Inorganic phosphate modifies stationary phase fitness and metabolic pathways in Lactiplantibacillus paraplantarum CRL 1905 - Araoz, Mario; Grillo-Puertas, Mariana; de Moreno de LeBlanc, Alejandra; Hebert, Elvira María; Villegas, Josefina María; Rapisarda, Viviana Andrea (Frontiers in Microbiology, 2024)
Phosphate (Pi) concentration modulates inorganic polyphosphate (polyP) levels in diverse bacteria, affecting their physiology and survival. Lactiplantibacillus paraplantarum CRL 1905 is a lactic acid bacterium isolated from quinoa sourdough with biotechnological potential as starter for initiating fermentation processes in food and antimicrobial-producing organism. The aim of this work was to evaluate the influence of the environmental Pi concentration on different physiological and molecular aspects of the CRL 1905 strain. Cells grown in a chemically defined medium containing high Pi (CDM+P) maintained elevated polyP levels up to late stationary phase and showed an enhanced bacterial survival and tolerance to oxidative stress. In Pi sufficiency condition (CDM-P), cells were ~25% longer than those grown in CDM+P, presented membrane vesicles and a ~3-fold higher capacity to form biofilm than those in CDM+P. Proteomic analysis indicated that proteins involved in the "carbohydrate transport and metabolism" and "energy production and conversion" categories were up-regulated in high Pi stationary phase cells, implying an active metabolism in this condition. On the other hand, stress-related chaperones and enzymes involved in cell surface modification were up-regulated in CDM-P medium. Our results provide new insights to understand the CRL 1905 adaptations in response to differential Pi conditions. The adjustment of environmental Pi concentration constitutes a simple strategy to improve the cellular fitness of L. paraplantarum CRL 1905, which would benefit its potential as a microbial cell factory.